Animal Histoplasmosis in Europe: Review of the Literature and Molecular Typing of the Etiological Agents - Wilmes, Dunja; Mayer, Ursula; Wohlsein, Peter; Suntz, Michael; Gerkrath, Jasmin; Schulze, Christoph; Holst, Ina; von Bomhard, Wolf; Rickerts, Volker (Journal of fungi (Basel), 2022)
Histoplasmosis has been previously diagnosed in animals from Europe. The aim of this study is to review the literature on these reports, to analyze cases diagnosed at our laboratory (2000–2022) and to improve molecular typing of Histoplasma capsulatum directly from tissue to study the molecular epidemiology of Histoplasma capsulatum causing animal infections in Europe. Including 15 cases studied in our laboratory, we identified 39 cases of animal histoplasmosis between 1968 and 2022. They were diagnosed mostly in superficial tissue biopsies from cats and badgers from Central Europe. Using phylogenetic analyses of six partial genes, we were able to classify eight of the etiological agents as belonging to a highly supported lineage within the Eurasian clade. This study confirms the occurrence of autochthonous histoplasmosis in animals in Central Europe and proposes the addition of new loci to the MLST scheme to study the molecular epidemiology of histoplasmosis using either formalin-fixed paraffin-embedded tissue and fresh or cadaveric biopsies.